Second-harmonic radiation by on-chip integrable mirror-symmetric nanodimers with sub-nanometric plasmonic gap - Hu Junzheng; Ye Xiaofei; Huang Hui; Su Guangxu; Lv Zhekai; Qin Zhaofu; Hu Pan; Liu Fanxin; Wu Wei; Zhan Peng (Nanophotonics)
Second-harmonic generation (SHG) facilitated by plasmonic nanostructures has drawn considerable attention, owing to its efficient frequency up-conversion at the nanoscale and potential applications in on-chip integration and nanophotonic devices. Herein, we present a nanodimer array fabricated by nanoimprinting, composed of nanofinger-pair symmetrically leaning at an off-angle with a well-defined sub-nanometric gap. Commonly, geometric symmetry would suppress the far-field SHG due to the near-field cancelling of symmetric surface SH polarization. However, we find that the light-induced surface SH polarization distribution along the wave-vector of incidence could be influenced by the off-angle, which is consistent to the requirement of SH polarization symmetry-breaking in symmetric metallic nanocavity. A dramatic enhancement of far-field SHG is achieved by tuning the off-angle of nanofinger-pair, even approaching up to over 4 orders of magnitude for an optimal value. The demonstration of SHG enhancement on our well-defined plasmonic nanodimer provides a new way of on-chip integration to activate high-efficient SH radiation, which might be potential for applications in novel nonlinear optical nanodevices with remarkable efficiency and sensitivity.